Does austerity work after all? The case of Latvia - Janssen, Ronald (Brussels, 2012)
" Latvia is used by the ‘austerians’ as a case showing that hard and painful austerity can get an economy out of recession. This policy brief argues the opposite and shows that what actually happened in Latvia is that policymakers decided not to continue but to break with the policy of austerity. This made it possible for Latvia to get out of a vicious spiral of austerity causing a depression and thereby leading to even more austerity.